2016
DOI: 10.1016/j.gheart.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Patterns, and Correlates of Physical Activity Among the Adult Population in Latin America: Cross-Sectional Results from the CESCAS I Study

Abstract: Objective Few data are available on population level regarding domain-specific correlates of physical activity (PA) in Latin America. The aim of this study was to examine the relationships among PA patterns and their main sociodemographic determinants and cardiovascular risk factors in the Southern Cone of Latin America. Methods CESCAS I is a population-based prospective cohort study with a 4-stage stratified sampling of a general population of 7,524 adults aged 35–74 years from four mid-sized cities in Arge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 34 publications
(34 reference statements)
2
30
0
4
Order By: Relevance
“…We found that women expended less energy than men in all age groups, mainly at expense of engaging in less intense activities. Previous research conducted in Latin America showed similar results, women were less likely to perform vigorous activities and to participate in leisure time PA and more prone to spend more time in household activities [22]. Similar patterns of PA were also described in women from developed populations [23,24].…”
Section: Discussionsupporting
confidence: 65%
“…We found that women expended less energy than men in all age groups, mainly at expense of engaging in less intense activities. Previous research conducted in Latin America showed similar results, women were less likely to perform vigorous activities and to participate in leisure time PA and more prone to spend more time in household activities [22]. Similar patterns of PA were also described in women from developed populations [23,24].…”
Section: Discussionsupporting
confidence: 65%
“…Another study, sampling only one section of Uruguay’s population, reported differences between sexes, with the lowest scores being among women, retirees, the unemployed, and homemakers [ 16 ]. Therefore, we hypothesised that cultural and social factors, as well as the family structure or past inequalities in education opportunities, could affect women’s participation in LTPA [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor diet and lack of PA are key risk factors for increasing and alarming levels of obesity in LACs [7,8]. However, most evidence to date has only been available from adult populations.…”
Section: Introductionmentioning
confidence: 99%